2015
DOI: 10.5194/acp-15-6789-2015
|View full text |Cite
|
Sign up to set email alerts
|

Influence of biomass aerosol on precipitation over the Central Amazon: an observational study

Abstract: Abstract. Understanding the influence of biomass burning aerosol on clouds and precipitation in the Amazon is key to reducing uncertainties in simulations of climate change scenarios with regard to deforestation fires. Here, we associate rainfall characteristics obtained from an S-band radar in the Amazon with in situ measurements of biomass burning aerosol for the entire year of 2009. The most important results were obtained during the dry season (July-December). The results indicate that the influence of aer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
63
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(81 citation statements)
references
References 62 publications
(93 reference statements)
11
63
0
7
Order By: Relevance
“…The observed associations in Fig. 3 are in line with the recent aerosol-cloud-rainfall association studies under continental conditions (Kourtidis et al, 2015;Myhre et al, 2007;Ten Hoeve et al, 2011), CTP Myhre et al, 2007;Yan et al, 2014), and rainfall (Gonçalves et al, 2015;Heiblum et al, 2012). These studies suggested that aerosolinduced changes in cloud dynamics and microphysics are the potential causal mechanism for the aerosol-cloud-rainfall linear dependence.…”
Section: The Effect Of Underrepresentation Of the Wet-scavenging Effesupporting
confidence: 77%
“…The observed associations in Fig. 3 are in line with the recent aerosol-cloud-rainfall association studies under continental conditions (Kourtidis et al, 2015;Myhre et al, 2007;Ten Hoeve et al, 2011), CTP Myhre et al, 2007;Yan et al, 2014), and rainfall (Gonçalves et al, 2015;Heiblum et al, 2012). These studies suggested that aerosolinduced changes in cloud dynamics and microphysics are the potential causal mechanism for the aerosol-cloud-rainfall linear dependence.…”
Section: The Effect Of Underrepresentation Of the Wet-scavenging Effesupporting
confidence: 77%
“…Accordingly, the life cycle of shallow and deep convective clouds in the Amazon has been subject of numerous previous studies (e.g., Andreae et al, 2004;Freud et al, 2008;Rosenfeld et al, 2016b;Wendisch et al, 2016;Braga et al, 2017). In particular, the extent of 10 anthropogenic influence on cloud lifecycle through continuous land use change and combustion-related aerosol emissions has been actively debated (Roberts et al, 2003;Davidson et al, 2012;Goncalves et al, 2015). It is well established that the properties and dynamics of clouds can be fundamentally altered by changing cloud condensation nuclei (CCN) regimes, which are a fraction of the total (tropospheric) aerosol population Reutter et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…14(b). Gonçalves et al (2015) analysed rainfall data in the Amazon and suggest that the influence of biomass burning on precipitation is dependent in part on the degree of atmospheric instability. In a more stable atmosphere, BBA tends to decrease the precipitation; they also note that increasing 10 cloud droplet number, and decreasing droplet size, would act to reduce precipitation in the absence of strong convection.…”
mentioning
confidence: 99%